2019
DOI: 10.1039/c8gc03876g
|View full text |Cite
|
Sign up to set email alerts
|

Solventless and metal-free regioselective hydrofluorination of functionalized alkynes and allenes: an efficient protocol for the synthesis of gem-difluorides

Abstract: A highly acidic fluorination system generated by DMPU-12HF and KHSO4-13HF can facilitate exclusive Markovnikov addition of HF to widely functionalized alkynes and allenes to produce gem-difluorides with an easy workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Continuing with more electron-deficient pyridinium salts, we found that the 2,6-dihalopyridinium salts (E and F) were more efficient reagents, with the more electron-deficient chlorinated reagent providing the desired product with good yield and excellent stereoselectivity (Z/E > 50:1, entry 6). We did not detect any gem-difluoride product from continued hydrofluorination of the monofluoroalkene, a process that could not be avoided under previous conditions using pyridine/HF or DMPU/HF 32,33 . We further found that yields could be enhanced by using and good selectivity for the opposite stereoisomer (E/Z = 11:1).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Continuing with more electron-deficient pyridinium salts, we found that the 2,6-dihalopyridinium salts (E and F) were more efficient reagents, with the more electron-deficient chlorinated reagent providing the desired product with good yield and excellent stereoselectivity (Z/E > 50:1, entry 6). We did not detect any gem-difluoride product from continued hydrofluorination of the monofluoroalkene, a process that could not be avoided under previous conditions using pyridine/HF or DMPU/HF 32,33 . We further found that yields could be enhanced by using and good selectivity for the opposite stereoisomer (E/Z = 11:1).…”
Section: Resultsmentioning
confidence: 64%
“…We next explored the scope of alkyl substituents on the substrate. A range of primary, secondary, cyclic or acyclic alkyl-substituted alkynes could be employed in the hydrofluorination to furnish respective products again with moderate to good yields and excellent regio-and stereoselectivities (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Remarkably, substrates with potentially sensitive functional groups including a primary chloro, a carboxymethyl, a cyano, a pyridyl, and a phthalimido group also delivered the monofluoroalkene products, highlighting the mildness and good functional group tolerance of this protocol (40)(41)(42)(43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…Thibaudeau demonstrated the applicability of the superacid HF‐SbF 5 in the hydrofluorination of ynamides at low temperatures, but it turned out that using pure anhydrous HF gave better yields . Finally, a stable ion exchange resin loaded with anhydrous HF reagent was developed by Hammond, allowing for a hydrofluorination of alkenes and functionalized alkynes and ring‐opening of aziridines …”
Section: Resultsmentioning
confidence: 99%
“…Under these optimized reaction conditions,w es et out to investigate the scope of this hydrofluorination reaction (Scheme 2). Using F for hydrofluorination, alkyl aryl acetylenes bearing electron-withdrawing (e.g., products 9, 19, 20, 22)t oe lectron-donating (e.g.,p roducts 23, 24, 25)a ryl substituents reacted effectively to afford the Z-configured fluoroalkene products in moderate to good yields and excellent regio-and stereoselectivities.M oreover,s everal common functional groups on the aryl ring, including amethyl ester (19), ac yano group (20), at rifluoromethanesulfonyl ester (22), and aphthalimide (23)were tolerated. Heteroaryl alkyl acetylenes,i ncluding an indole and af uran likewise delivered the desired product (24,25).…”
Section: Substrate Scopementioning
confidence: 99%
“…[19] More recent studies by Hammond, Xu, and co-workers led to the development of several designer base-complexed sources of hydrogen fluoride. [20] However,b oth reports indicate that, in general, even with careful control of the reaction temperature (0 to 50 8 8C), HF-amine reagents deliver the gem-difluoride bis(hydrofluorination) product (Scheme 1Bb), without allowing isolation of the presumed vinyl fluoride intermediate,e xcept in special cases where the alkyne bears ad onor heteroatom substituent (e.g., ynamide [21] or alkynyl sulfide substrates [22] ).…”
Section: Introductionmentioning
confidence: 99%